Estudo químico de fungos endofíticos associados a plantas do bioma caatinga. - Oliveira, Francisco Carlos de (2017)
The chemical study of endophytic fungi associated with plants of the Caatinga biome was carried out through the identification of volatile organic compounds (VOCs) and the isolation of non-volatile metabolites produced by ten fungi of the family Botryosphaeriaceae and one of the family Nectriaceae. In the identification of VOCs produced by the fungus Albonectria rigidiuscula (Nectriaceae), four different culture media (BD, BDA, peptone and rice) and three incubation periods (7, 14 and 21 days) were used, using the same techniques of extraction and analysis. In the study of identification of VOCs, the fungi were: L. gonubiensis, L. parva, L. pseudotheobromae, L. theobromae, Neosicoccum ribis, N. cordaticola, N. parvum, Botrysphaeria mamane and Pseudofusicoccum stromaticum cultivated in BD under the same conditions. As extraction and analytical technique, headspace solid phase microextraction (SPME-HS), coupled with gas chromatography coupled to mass spectrometry (GC-MS), was used. The data of the analyzes were also submitted to statistical treatments of PCA and HCA. The identification of fungal VOCs was adequate to discriminate ten species of the family Botryosphaeriaceae. The discrimination of the N. parvum / N. Ribis pointed out the importance of VOCs as an auxiliary chemotaxonomic tool. In addition, α-bisabolol, which was produced at high level (88.83%) by the P. stromatium fungus, can be identified as a chemical marker for this specie. The production of VOCs by the A.rigidiuscula fungus showed greater qualitative and quantitative variations in nutrient poor media. The fungi N.parvum, L. gonubiensis and A. rigidiuscula presented cytotoxic potential and the study of non-volatile compounds showed significant variations in the fatty acids produced in the mycelia and extracted liquid media. The metabolites (3S, 4S)-4-hydroxymellein, cyclic (Leu-Pro), cyclic (S-Phe-S-Pro), (3S, 4R)-4-hydroxymellein mellein, pestalopyrone, xylitol, cyclo (L-Pro-L-Tyr) and tyrosol. The isolation of diketopiperazines suggests a relationship of these compounds with the cytotoxic potential of active extracts, since the anticâncer potential of this class is reported in the literature.